2004
DOI: 10.1016/s0736-0266(03)00117-7
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte apoptosis induced by collagen degradation: Inhibition by caspase inhibitors and IGF‐1

Abstract: The main objective of this study was to test the effectiveness of candidate apoptosis inhibitors in limiting chondrocyte apoptosis induced by collagen degradation. Primary human chondrocytes were isolated from normal articular cartilage and grown in monolayer culture. Collagenase was added to the cells in the presence and absence of caspase inhibitors and insulin like growth factor (1GF)-I . The amount of chondrocyte apoptosis was measured using an enzyme linked immunosorbent assay for nucleosomes, a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 19 publications
0
57
1
2
Order By: Relevance
“…40 The addition of IGF-1 to explants and monolayer cultures at concentrations of 10-200 ng/mL increased collagen type II and DNA synthesis and inhibited proteoglycan degradation, 41 whereas 200 ng/mL also inhibited chondrocyte apoptosis in vitro. 42 The optimal dose of IGF-1 required to enhance proteoglycan synthesis in osteoarthritic cartilage was 30 ng IGF-1/mL. 43 Previous research also indicated that in vitro chondrocytes do not respond any better to 1000 ng IGF-1/mL than 100 ng IGF-1/mL.…”
mentioning
confidence: 99%
“…40 The addition of IGF-1 to explants and monolayer cultures at concentrations of 10-200 ng/mL increased collagen type II and DNA synthesis and inhibited proteoglycan degradation, 41 whereas 200 ng/mL also inhibited chondrocyte apoptosis in vitro. 42 The optimal dose of IGF-1 required to enhance proteoglycan synthesis in osteoarthritic cartilage was 30 ng IGF-1/mL. 43 Previous research also indicated that in vitro chondrocytes do not respond any better to 1000 ng IGF-1/mL than 100 ng IGF-1/mL.…”
mentioning
confidence: 99%
“…Although a variety of different stimuli initiate chondrocyte apoptosis [2,3,6,9,10,23,24,26,30,32], a universal feature of chondrocyte apoptosis is caspase activation [13,16,17,31,35,39,44] (Fig. 1).…”
Section: Chondrocyte Apoptosis Regulation Pathwaysmentioning
confidence: 99%
“…Upon activation, caspase enzymes cleave a number of cellular proteins, including poly (ADPribose) polymerase, sterol regulatory element binding protein, and nuclear mitotic apparatus proteins, which ultimately lead to cell death. In particular, caspase 1 and caspase 3 are believed to play critical roles in the initiation and execution phases of chondrocyte apoptosis, making them attractive targets for intervention [31]. Caspase 9, part of the ''apoptosome'' complex that mediates mitochondrial pro-apoptotic signaling pathways, may also play an important role in chondrocyte apoptosis [35].…”
Section: Chondrocyte Apoptosis Regulation Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations